2022
DOI: 10.1021/acsanm.2c00218
|View full text |Cite
|
Sign up to set email alerts
|

MnO2 Nanowires Decorated with Au Nanoparticles for Plasmon-Enhanced Electrocatalytic Detection of H2O2

Abstract: MnO2 is a cheap and versatile material, being able to act as a catalyst for different electrochemical reactions. The addition of small amounts of Au nanoparticles (NPs) enables the possibility to explore the localized surface plasmon resonance (LSPR) effect to improve the photocatalytic properties of MnO2. The LSPR effect can accelerate several reactions under visible light irradiation, improving the charge separation and light harvesting properties of semiconductors. Here, by employing MnO2 nanowires decorate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…These results are even better than those of composites containing Au NPs and enhanced with the LSPR effect in the literature (Table 2). [44][45][46][47][48] In order to better use the CZIF/Au, the catalytic stability of H 2 O 2 was tested at 655 nm. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These results are even better than those of composites containing Au NPs and enhanced with the LSPR effect in the literature (Table 2). [44][45][46][47][48] In order to better use the CZIF/Au, the catalytic stability of H 2 O 2 was tested at 655 nm. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that MnO 2 nanostructures could catalyze degradation of H 2 O 2 into water and O 2 in a tumor acidic environment, so as to alleviate the tumor hypoxic microenvironment. [18][19][20] Meanwhile, MnO 2 nanostructures can also undergo a redox reaction with GSH to yield Mn 2+ and glutathione disulfide (GSSG), thus scavenging GSH in cancer cells. 21 The generated Mn 2+ ions could significantly enhance T1-magnetic resonance (MR) imaging contrast for tumor-specific imaging.…”
Section: Introductionmentioning
confidence: 99%